Revealing the Dark Veil of Illegal Business - Nafsiah, Maqfira Izzata; Edytya, Nindya Putri; Bagas Tony, Masyita Isnadya Risky Salsabila Putri; Rahmatika, Aulia Vaya (Law Research Review Quarterly, 2020)
Prostisusi becomes one of the social problems that continues to develop over time. Various internal and external factors trigger this activity to continue to exist until now. This research examines the business of prostitution as a form of disease in society and social problems. This research tries to reveal the karaoke business under the guise of illegal prostitution business, especially in Central Java. This research uses the approach of Criminal Law, Criminology, and Social Structure. The research method used is qualitative research, where the writer directly looks at existing social phenomena and seeks field facts through observation, interviews, and investigations. This research found that various factors become the background of the existence of the karaoke business under the guise of illegal prostitution in Central Java, ranging from economic and business factors to weak rules and law enforcement. The study also revealed the fact that the karaoke business secretly provided sex or prostitution services, but law enforcement was ineffective. One of the ineffectiveness of law enforcement is the problem of law enforcement apparatuses and bribery resources that occur within the law enforcement environment. In addition, this business also deals directly with business and economic investment holders.